Hazard Identification and Exposure Assessment for Wastewater Management Workers - Miftakhul Nurdiyanto; Tri Joko; Mursid Raharjo (GLOBAL HEALTH SCIENCE GROUP, 2025)
Sanitation workers in hospitals are at high risk of developing health disorders due to direct exposure to wastewater during the operation and maintenance of wastewater treatment plants (WWTP). This study aims to identify the types of health problems experienced by 33 sanitation personnel at Sentra Medika Cibinong Hospital and to analyze the contribution of wastewater treatment processes to these health risks using the Life Cycle Assessment (LCA) approach. Methods: This study employed a qualitative descriptive method using a Life Cycle Assessment (LCA) approach. From a total population of 33 individuals, the researcher selected all 33 as the study sample. Data were analyzed using both quantitative and qualitative approaches. Additionally, the Life Cycle Assessment (LCA) methodology was employed to identify environmental impacts and potential health risks arising from the hospital's wastewater management system. Results: The results showed that 87.9% of the workers reported health complaints, including skin irritation, respiratory symptoms (shortness of breath, coughing), dizziness, nausea, vomiting, and gastrointestinal disorders. The highest exposure occurred during chemical dosing, sludge pit cleaning, and wastewater sampling. The LCA results indicated that the aeration and disinfection stages contributed significantly to hazardous emissions such as hydrogen sulfide (H₂S), chlorine, and fine particulates, which can pose serious health risks. Conclusion: This study highlights the urgent need to improve occupational health protection through proper use of personal protective equipment (PPE), routine training, and redesigning WWTP systems to be more worker-friendly. LCA proved to be an effective tool in identifying health-related risk hotspots throughout the wastewater management cycle.